Поняття та ознаки корупції та корупційних злочинів - Музичук, О. М.; Muzychuk, O. M.; Лук'яненко, С. В.; Lukianenko , S. V. (Європейські перспективи. - 2023. - № 2. - С. 167-171, 2023)
Запропоновано авторське визначення поняття корупції. Акцентовано увагу на особливій небезпечності корупції, як соціально-економічного явища. Відмічено, що корупція являє собою зловживання посадовими особами своїм становищем у цілях отримання особистої вигоди або вигоди для свого оточення за рахунок підкупу, вимагання хабарів, використання владних повноважень та інших дій, що порушують етичні та законні норми. Надано визначення поняття корупційного злочину, на основі чого виокремлено його найбільш характерні ознаки.

It was noted that corruption is the abuse by officials of their position in order to obtain personal benefit or benefit for their environment through bribery, extortion of bribes, use of power and other actions that violate ethical and legal norms. Corruption can manifest itself in various spheres of public life, including politics, business, law enforcement, the judicial system, medicine, education, construction, and others. Corruption is a threat to democracy, human rights, economic growth and development of society as a whole. It was emphasized that the crime of corruption is a violation of the rules and norms of criminal legislation that regulate issues of government activity, which are aimed at obtaining an illegal benefit. Corruption crimes may include actions aimed at illegally obtaining money, material goods or other forms of benefit. The following key features of a corruption crime are highlighted: special public danger, which distinguishes corruption crimes from other corruption offenses, because it always creates a threat of significant harm to individuals and/or legal entities, as well as to society and the state as a whole; the procedure for prosecution for committing corruption crimes is regulated by the Criminal Code of Ukraine; a corruption crime is characterized by all the signs of corruption outlined in Article 1 of the Law of Ukraine “On Prevention of Corruption”; the crime of corruption can be committed exclusively by an official who is endowed with powerful powers and involves the use of his official position; an exclusively intentional form of guilt, however, the attitude to the consequences can be expressed both in the form of intent and in the form of carelessness.

Предложено авторское определение понятия коррупции. Акцентировано внимание на особой опасности коррупции как социально-экономического явления. Отмечено, что коррупция представляет собой злоупотребление должностными лицами своим положением в целях получения личной выгоды или выгоды для окружающих за счет подкупа, вымогательства взяток, использования властных полномочий и других действий, нарушающих этические и законные нормы. Дано определение понятия коррупционного преступления, на основе чего выделены его наиболее характерные признаки.
Keywords: корупція; corruption; коррупция; корупційні злочини; corruption crimes; коррупционные преступления; посадова особа; official; должностное лицо; кримінальне законодавство; criminal legislation; уголовное законодательство